Determinants of Audit Fees - El-Gammal, Walid (2012)
This paper studies the views of external auditors and client's representatives (accountants, financial controllers and internal auditors) about the factors that affect determining audit fees and provides evidence whether these factors are related to audit firm characteristics or the client firm characteristics. A sample of 80 respondents provided the empirical data for this research by answering a self administered questionnaire. To conduct data analysis descriptive statistics, means, standard deviation and Mann-Whitney U test were used. The outcome of the study provides a vital insight into the determinants of audit fees from a developing country like Lebanon. It was found that all the pre-suggested determinants of audit fees are extremely important or important. Both external auditors and client representatives groups agree that the most important factor affecting determining amount of audit fees is whether the audit firm is one of the big four or notand the least important factor is the size of the audit firm based on the number of its employees. The results also show that the degree of importance of each determinant of audit fees is homogenous among the two groups of respondents